Adverse reactions associated with meningococcal group B vaccine (4CMenB) in adults in special situations - María Fernández-Prada; Carmen Martínez-Ortega; Lara Hidalgo-Peña; Clara Álvarez-Vázquez; Rodrigo Aguirre-del Pino; Ismael Huerta-González (Farmacia Hospitalaria)
Objective: To know the safety profile of the 4CMenB vaccine in adults in special situations. Method: Security prospective study of phase IV. Inclusion criteria and some vaccination conditions were applied. The adverse reactions described in the data sheet were collected. The adverse reactions evaluation was performed 24 hours after vaccination (“requested”) and during the first seven days (“not requested”). Results: 72 patients were included (54.2% men, mean age 52.5 years, 81.9% anatomic asplenia). The frequency of fever > 38 ºC in the first 24 hours of vaccination was higher than the observed in the summary of product characteristics for the group of adults (12.5% vs. not known). More than 75% of the patients reported local pain in the first hours [average of the Analog Visual Scale score 3.22 (95% CI: 2.67-3.76) in the first dose and 3.23 (95% CI: 2.69-3.78) in the second dose]. There were no statistically significant differences. 97.22% registered symptoms until 7 days after vaccination. Conclusions: 4CMenB® shows a good safety profile in adults in special situations. The frequency of fever > 38 ºC is higher than expected. Local pain is the most frequently recorded adverse reactions, but the intensity is low. These results suggest a review of the situation in order to suggest a possible modification of the summary of product characteristics of the vaccine.